The determinants factors of sucessful franchise business in Malaysia - Mohd Harif, Mohd Amy Azhar; Othman, Siti Norezam; Md Isa, Filzah; Din, Mohd Salleh; Hoe, Chee Hee; Hussein, Zulkifli (World Business Institute Australia ABN, 2010)
The objective of this research is to identify the critical success factors of Bumiputera and non-Bumiputera franchisors in conducting their franchise business in Malaysia. The cross case study approach was used to analyse the data. Thirteen franchisors (6 Bumiputera and 7 non-Bumiputera) were selected as the sample cases. There were two important variables which had been identified as very critical to the success of local franchise business namely marketing orientation factors and entrepreneurial based factors. The Bumiputra franchisors highlighted competition as their main business market orientation, while non-Bumiputera franchisors scored high for customer orientation in product dominant sector. Both of the ethnics demonstrated high entrepreneurial based factors. For the service dominant sector, the non Bumiputra franchisors emphasized on customer and competition orientation, whereas, the Bumiputra franchisors stressed more on customer and interfunctional coordination. However, the Bumiputra franchisors scored moderate achievement motivation and low risk taking as well as innovation. The non Bumiputra franchisors scored high in the entrepreneurial based factors.